2003
DOI: 10.2746/042516403775467225
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic surgery in the treatment of contaminated and infected synovial cavities

Abstract: Summary Reasons for performing study: Contamination and infection of synovial cavities are a common occurrence in clinical practice and, if inadequately treated, may have career or life threatening consequences for affected horses. Hypothesis: The objectives in treating contamination and infection of joints, tendon sheaths and bursae are most effectively met by endoscopic surgery. Methods: Over a 6 year period, cases of synovial contamination and infection admitted to a referral clinic were evaluated and tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
204
12
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(243 citation statements)
references
References 29 publications
21
204
12
6
Order By: Relevance
“…It was our purpose to be as specific as possible when defining sepsis in a synovial structure and to evaluate septic synovitis and nonseptic contaminated intrasynovial lacerations separately. Previous studies 15,24,[33][34][35][36][37][38][39] evaluating septic synovitis in horses have found survival rates of 62% to 92% in adults and 42% to 85% in foals. In our study, 72% of horses with septic synovitis were discharged from the hospital, and 53.43% of the horses with follow-up information available were alive at long-term follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…It was our purpose to be as specific as possible when defining sepsis in a synovial structure and to evaluate septic synovitis and nonseptic contaminated intrasynovial lacerations separately. Previous studies 15,24,[33][34][35][36][37][38][39] evaluating septic synovitis in horses have found survival rates of 62% to 92% in adults and 42% to 85% in foals. In our study, 72% of horses with septic synovitis were discharged from the hospital, and 53.43% of the horses with follow-up information available were alive at long-term follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…In contaminated synovial cavities the objectives of surgical treatment are the removal of foreign material, debridement of contaminated and devitalised tissue, elimination of microorganisms, removal of destructive enzymes and free radicals, promotion of tissue healing and restoration of a normal synovial environment (Wright et al 2003). Lavage of the synovial cavity is the treatment of choice.…”
Section: Discussionmentioning
confidence: 99%
“…There is also general consensus in the veterinary literature that the keys to successful treatment of horses with septic synovitis are early recognition and prompt treatment (Nixon 1990, Chan et al 2000, Fraser and Bladon 2004, Wright et al 2003. In a recent retrospective study, the outcome was considered successful (survival without residual lameness) in 109 of 150 horses (72.7%) with contaminated and infected synovial cavities (Pille et al 2009).…”
mentioning
confidence: 99%
“…In horse, tenovaginoscopy of the CDFTS is used for diagnosis and treatment of aseptic and septic digital tenosynovitis, release of the lig. anulare palmare/plantare, and it is useful in lavage, adherence debridement, removal of foreign material and devitalised tissue (Nixon, 1990;Frees et al, 2002;Nixon, 2002;Wright et al, 2003;Fraser and Bladon, 2004;Edinger et al, 2005;Lopes et al, 2006). The entry portal for routine tenovaginoscopy of the CDFTS is on the palmarolateral/plantarolateral surface immediately distal to the lig.…”
Section: Arthroscopymentioning
confidence: 99%
“…In treating joint infection in man, arthroscopy is considered to offer several advantages over lavage and arthrotomy including improved visualization, identification of foreign material and infected or devitalized tissue, and access to a large area of synovial surfaces. Arthroscopy ensures an efficiently evaluated, cleaned, debrided and decompressed joint with minimal morbidity, reduced period of hospitalization and maximal functional recovery compared to other treatments (Wright et al, 2003). Also in cattle, arthroscopy has been described as an alternative minimal invasive diagnostic procedure in complicated arthritis, and it allows treatment of the joint cavity too (Munroe and Cauvin, 1994;Gaughan, 1996;Steiner et al, 1999;Starke et al, 2008).…”
Section: Introductionmentioning
confidence: 99%